Strategy for the Management of Bacterial Spot of Bot tle Gourd Caused by Xanthomonas cucurbitae under Low Hill Condit ions of Himachal Pradesh - Jarial, Kumud; Jarial, R. S.; Sharma, Deepa; Dogra, B. S.; Kumar, Sunil (International Journal of Bio-resource and Stress Management, 2023)
To manage the bacterial spot of bottle gourd caused by Xanthomonas cucurbitae, experiments were conducted at College of Horticulture and Forestry (then Institute of Biotechnology and Environmental Science), Neri Hamirpur (HP) during 2010, 2011 and 2012 cropping seasons. Five chemicals viz., zineb, Bodeaux mixture, mancozeb, copper oxychloride and streptocycline were evaluated as foliar sprays on bottle gourd grown under field conditions during 2010. Minimum disease severity (28.33%) and maximum disease control (68.45%) was recorded in Streptocycline treated plants followed by copper oxychloride. During 2011, naturally infected seed was treated with streptocycline (100 ppm) and copper oxychloride (3000 ppm) alone and in combination with each other for 1.0, 2.0 and 3.0 hours. Seeds treated for three hours in combination of streptocycline and copper oxychloride proved best in terms of seed germination and exclusion of bactria. During 2011, effective seed treatment and foliar sprays were evaluated alone or in combinations under natural conditions on six genotypes of bottle gourd. Mean disease severity in all genotypes of bottle gourd ranged between 33.75 to 35.83%, while, a combination of seed treatment with streptocycline (0.01%)+copper oxychloride (0.3%) for 3.0 h and foliar spray with the same combination resulted in significantly minimum disease severity (20.56%) and maximum disease control (76.34%). During 2012 crop season, spray interval of two effective treatments was standardized in combination with removal of diseased plant parts. Above seed treatment followed by the spray of streptocycline (0.01%)+copper oxychloride (0.3%) at 10 days interval alongwith the removal of diseased plant parts proved most effective in managing (78.35% disease control) the disease (20.17%) in comparison to untreated control.